Uji Validitas Konstruk Instrumen MARS-30 dalam Mengukur Kecemasan Matematika Siswa Melalui Simulasi Monte Carlo - Zulkarnain Zulkarnain; Salnia Ramadani (Lembaga Pengembangan Kinerja Dosen, 2025)
Mathematics anxiety is a psychological barrier that negatively affects students’ performance and self-confidence. A valid and reliable measurement tool is required to identify this condition accurately. This study aims to examine the construct validity of the Mathematics Anxiety Rating Scale 30 (MARS-30) using a Monte Carlo simulation approach. The research employed first-order confirmatory factor analysis (CFA) through R software with a simulated sample of 300 respondents. The findings revealed that the overall measurement model achieved excellent fit indices, as indicated by Normed χ², RMSEA, SRMR, and CFI, all within the optimal range. Nevertheless, only 8 out of 30 items (26.7%) met the validity criteria, while the remaining 22 items were found invalid. This result suggests that although the global model fit was adequate, most items of MARS-30 did not consistently represent the construct of mathematics anxiety. The implication of this study highlights the necessity of revising the instrument by refining item wording, adjusting indicators, and conducting further testing to ensure stronger construct validity. A more valid instrument will enable educators and researchers to design targeted pedagogical interventions for reducing mathematics anxiety and supporting students’ learning outcomes.